1974
DOI: 10.1071/ar9740899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autumn on the induction of dormancy in apple and peach seedlings and their subsequent regrowth in spring

Abstract: Apple and peach seedlings were grown for 8 weeks under various regimes: two photoperiods (16 and 8 hr), two air temperatures (12.8° and 18.3°C) and three root temperatures (12.8°, 18.3° and 23.9°C). After the leaves were removed the seedlings were chilled in the dark at 5.6° for three periods (apples 750, 1500 and 2500 hr; peaches 750, 1500 and 2000 hr) and then grown in a glasshouse for 7 weeks during which bud break and extension growth were measured. Growth of apple seedlings (cv. Granny Smith) stopped in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…It has been reported that warm periods during pre-chilling result in reduced bud break in peaches (Nichols et al, 1974) and that extended chilling results in reductions in the heat requirements of peach buds (Citadin et al, 2001;Scalabrelli and Couvillon, 1986). Furthermore, in our experiment there was signif- Table 4.…”
Section: Comparison Of Calculated and Observed Blooming Dates Of Foursupporting
confidence: 64%
See 1 more Smart Citation
“…It has been reported that warm periods during pre-chilling result in reduced bud break in peaches (Nichols et al, 1974) and that extended chilling results in reductions in the heat requirements of peach buds (Citadin et al, 2001;Scalabrelli and Couvillon, 1986). Furthermore, in our experiment there was signif- Table 4.…”
Section: Comparison Of Calculated and Observed Blooming Dates Of Foursupporting
confidence: 64%
“…The data obtained in this experiment were likely to be affected by many environmental factors at each location and during each season. For example, it has been reported that bud break of peach and nectarine may be influenced by photoperiod (Nichols et al, 1974) and water conditions (Gilreath and Buchanan, 1981a) as well as temperature. It is also possible that the high RMSE values were affected by differences in temperature between the research locations and their neighboring AMeDAS observatories.…”
Section: Comparison Of Calculated and Observed Blooming Dates Of Fourmentioning
confidence: 99%
“…Chilling intact 'Delicious' trees 6 and 8 weeks before bud explants were taken resulted in greater bud burst than the longer chilling periods of 14 and 21 weeks. In contrast, other workers (10,14) have reported that 14 weeks chilling was more effective than shorter chilling periods for promoting growth of buds on intact trees of other cultivars. Why bud burst declined with longer chilling periods in the present experiments with 'Delicious' is not clear.…”
Section: Discussionmentioning
confidence: 68%
“…O efeito das baixas temperaturas por um período mais prolongado (2.500 horas) já havia sido revelado por Nichols et al (1974), ocasionando maior brotação e crescimento das mudas de macieira da cultivar Granny Smith. Ribas & Zanette (1992) também observaram os efeitos positivos das baixas temperaturas sobre o crescimento de mudas de macieira durante a aclimatização.…”
Section: Resultsunclassified